The Patriarch’s Balls: Class-Consciousness, Violence, and Dystopia in George Saunders’ Vision of Contemporary America - Juliana Nalerio (Miscelánea: A Journal of English and American Studies, 2015)
In late 19th Century America, the elite of wealthy New York families were united by the Patriarch’s Balls. The Society of the Patriarch organized lavish balls to foster a content class-consciousness among the society of “The Four Hundred” who mattered, in contrast to the rest who did not. In 21st Century America, the tables have been turned and the class conscious are less able to enjoy the fruits of their labor sans guilt (or the realization of a nasty pun). As Slavoj Zizek asserts in Six Sideways Glances on Violence, contemporary America’s “culture of capital” is marked by the systemic violence that allows the West to maintain its First World status and North American writer George Saunders, for one, knows it. This paper will look at how Saunders returns to those East Coast, greater New York communities in the 21st Century, communities that are now more egalitarian and “open” yet just as worried about keeping up with the Joneses. Writing their stories with a dystopic twist, he intimately explores the anxieties that plague their communities, while also maintaining a sense of the universal in his work that allows for its wider interpretation and relevance to the American national identity in general. Saunders writes as the moral conscience of a community that while “successful” according to American standards, cannot help but feel all the dirtier after the help have cleaned the kitchen.